1986
DOI: 10.1271/bbb1961.50.157
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the subunit protein of bipyramidal .DELTA.-endotoxin produced by Bacillus thuringiensis kurstaki strain HD-1.

Abstract: The structure of the subunit protein of the bipyramidal Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…A similar effect was observed in vitro where lepidopteran midgut-membrane vesicles challenged with activated toxin exhibited morphological changes and swelling (Tojo, 1986). Subsequent investigations have shown that CryI toxins alter the permeability of lepidopteran midgut apical membranes for monovalent cations (Sacchi et al, 1986;Crawford and Harvey, 1988;Wolfersberger, 1989;Hendrickx et al, 1990).…”
mentioning
confidence: 59%
“…A similar effect was observed in vitro where lepidopteran midgut-membrane vesicles challenged with activated toxin exhibited morphological changes and swelling (Tojo, 1986). Subsequent investigations have shown that CryI toxins alter the permeability of lepidopteran midgut apical membranes for monovalent cations (Sacchi et al, 1986;Crawford and Harvey, 1988;Wolfersberger, 1989;Hendrickx et al, 1990).…”
mentioning
confidence: 59%
“…The organism produces parasporal crystals, which are comprised of two polypeptides, P1 and P2, having endotoxic activity against lepidopteran and dipteran larvae (7,21). In recent years much research has been devoted to the isolation of the specific toxin-encoding genes and determination of their nucleotide sequences (14,19,20). However, with the advent of gene fusion and site-specific mutagenesis techniques, it has become important to transport genetically constructed molecules into B. thuringiensis.…”
mentioning
confidence: 99%
“…A total of 42 fifth-instar larvae of the silkworm (mean body weight, 580 mg) were used. Each larva was force fed with 10 p.g of inclusions containing approximately 2 ,ug of P-59 (20). At specified intervals between 5 and 240 min, 50 p.l of hemolymph was collected from each larva, and the larvae were discarded after this bleeding.…”
mentioning
confidence: 99%
“…At specified intervals between 5 and 240 min, 50 p.l of hemolymph was collected from each larva, and the larvae were discarded after this bleeding. The hemolymph was diluted with 150 p. of PBS containing 1% bovine serum albumin, and the presence of P-59 antigen was examined by an enzyme-linked immunosorbent assay (ELISA) as described previously (20). The sensitivity limit of the assay for determination of P-59 in the hemolymph was 1.6 ng/ml.…”
mentioning
confidence: 99%